Cross‐scale observations of the 2015 St. Patrick's day storm: THEMIS, Van Allen Probes, and TWINS. Issue 1 (20th January 2017) - Goldstein, J.; Angelopoulos, V.; De Pascuale, S.; Funsten, H. O.; Kurth, W. S.; LLera, K.; McComas, D. J.; Perez, J. D.; Reeves, G. D.; Spence, H. E.; Thaller, S. A.; Valek, P. W.; et al.
Abstract: We present cross‐scale magnetospheric observations of the 17 March 2015 (St. Patrick's Day) storm, by Time History of Events and Macroscale Interactions during Substorms (THEMIS), Van Allen Probes (Radiation Belt Storm Probes), and Two Wide‐angle Imaging Neutral‐atom Spectrometers (TWINS), plus upstream ACE/Wind solar wind data. THEMIS crossed the bow shock or magnetopause 22 times and observed the magnetospheric compression that initiated the storm. Empirical models reproduce these boundary locations within 0.7  R E . Van Allen Probes crossed the plasmapause 13 times; test particle simulations reproduce these encounters within 0.5  R E . Before the storm, Van Allen Probes measured quiet double‐nose proton spectra in the region of corotating cold plasma. About 15 min after a 0605 UT dayside southward turning, Van Allen Probes captured the onset of inner magnetospheric convection, as a density decrease at the moving corotation‐convection boundary (CCB) and a steep increase in ring current (RC) proton flux. During the first several hours of the storm, Van Allen Probes measured highly dynamic ion signatures (numerous injections and multiple spectral peaks). Sustained convection after ∼1200 UT initiated a major buildup of the midnight‐sector ring current (measured by RBSP A), with much weaker duskside fluxes (measured by RBSP B, THEMIS a and THEMIS d). A close conjunction of THEMIS d, RBSP A, and TWINS 1 at 1631 UT shows good three‐way agreement in the shapes of two‐peak spectra from the center of the partial RC. A midstorm injection, observed by Van Allen Probes and TWINS at 1740 UT, brought in fresh ions with lower average energies (leading to globally less energetic spectra in precipitating ions) but increased the total pressure. The cross‐scale measurements of 17 March 2015 contain significant spatial, spectral, and temporal structure. Key Points: Observations by THEMIS, Van Allen Probes, and TWINS contain much spatial, spectral, and temporal variation During main phase, all three missions measured two‐peak ion spectrum in center of partial ring current Encounters with bow shock, magnetopause (by THEMIS) and plasmapause (RBSP) reproduced by models